Teprotumumab Treatment for Thyroid Eye Disease in a Patient with Pre-Existing Hearing Loss: Worth the Risk? - Wyatt Hyke; Cheryl Polinsky; Lisa Schifanella (CRO (Clinical & Refractive Optometry) Journal, 2026)
Thyroid eye disease (TED) can lead to reduced vision from corneal scarring or optic nerve compression. Other manifestations of thyroid eye disease that can be troubling for TED patients include proptosis, extraocular muscle restrictions and diplopia, soft tissue swelling, dry eye, and conjunctival injection over the extraocular muscle insertions. Intravenous teprotumumab was approved by the Food and Drug Administration (FDA) in 2020 for the treatment of active TED. Teprotumumab can cause potentially permanent severe hearing problems, including hearing loss and tinnitus. For those with preexisting hearing impairment, further hearing loss could have a serious impact on activities of daily living. Herein, we report a case of a patient with known sensorineural hearing loss who uses a hearing aid and chose to receive teprotumumab infusions for his active TED. This case will discuss TED, teprotumumab, and its side effects, including hearing loss, and important considerations for patient education for patients with pre-existing hearing loss who are considering teprotumumab infusions.